STOCHASTIC FINITE ELEMENT MODEL UPDATING BASED ON POLYNOMIAL CHAOTIC EXPANSION AND KL DIVERGENCE - XU ZeWei; PENG ZhenRui; ZHANG YaFeng; BAI Yu (Jixie qiangdu)
Considering the influence of structural parameter uncertainty on response and the problem of large calculation of stochastic model updating, a stochastic finite element model updating method based on polynomial chaotic expansion and KL divergence is proposed. Firstly, Kriging model is constructed instead of finite element model analysis, then polynomial chaotic expansion model is constructed based on probabilistic collocation method and regression analysis, and the functional relationship between uncertain structural parameters and response is established to quickly estimate the mean value and standard deviation of response. Finally, the mean value and standard deviation of structural parameters are modified to minimize KL divergence. Taking three-dimensional truss as an example, the mean value and standard deviation of elastic modulus and density are modified to verify the feasibility of the proposed method. The results show that the proposed method has high updating accuracy and efficiency.